2007
DOI: 10.1515/znc-2007-1-206
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols of Rosa L. Leaves Extracts and their Radical Scavenging Activity

Abstract: Antioxidant potential of Rosa L. leaves methanolic extracts was evaluated in vitro using a spectrophotometric method based on measuring the radical scavenging effect on 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals. The contents of ellagic acid, quercetin and kaempferol in the extracts from leaves of seventeen rose species were determined using SPE-RP-HPLC methods. Additionally, total phenolic content was determined spectrophotometrically according to the Folin-Ciocalteu procedure and calculated as gallic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 29 publications
9
66
2
1
Order By: Relevance
“…In our study Acta Alimentaria 44, 2015 increase of total polyphenolic content was followed by a slight increase in the content of quercetin in all studied onion cultivars, however, without statistical differences (P>0.05). Our results differ from those published by NOWAK and GAWLIK-DZIKI (2007), where the authors found statistically signifi cant positive correlation between quercetin and total fl avonols content. The results of the present study require further experiments to complete the whole task.…”
Section: Resultscontrasting
confidence: 99%
“…In our study Acta Alimentaria 44, 2015 increase of total polyphenolic content was followed by a slight increase in the content of quercetin in all studied onion cultivars, however, without statistical differences (P>0.05). Our results differ from those published by NOWAK and GAWLIK-DZIKI (2007), where the authors found statistically signifi cant positive correlation between quercetin and total fl avonols content. The results of the present study require further experiments to complete the whole task.…”
Section: Resultscontrasting
confidence: 99%
“…The free radical scavenging activity of the isolated compound was estimated according to the procedure described by Brand-Williams, Cuvelier & Berset (1995) with some modifications [23,24]. Ethanol of analytical grade (POCH, Poland), 1,1-diphenyl-2-picrylhydrazyl radical -DPPH .…”
Section: Antioxidant Assaymentioning
confidence: 99%
“…The absorbance was measured at 517 nm after incubating the mixture at room temperature for 30 min in the dark. The antiradical activity was expressed as EC 50 (antiradical dose required to cause a 50% inhibition), which was calculated by the following formula: [(A blank − A sample )/A sample ] × 100, where A blank is the absorbance of the DPPH radical solution and A sample is the absorbance of the DPPH radical solution after the addition of the sample [24]. EC 50 was obtained by linear regression analysis of the dose-response curve, plotted between % inhibition and concentration (µg/ ml).…”
Section: Antioxidant Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The functional properties of some Rosa species were attributable to a wide array of bioactive ingredients such as minerals, fatty acids, volatile oils, ascorbic acid, phenols, flavonoids, tannins and sugar [7][8][9][10][11] . Despite the substantial data on the phytochemistry of some Rosa species namely R. canina, there are a dearth of information about the chemical constituents of Rosa x alba.…”
Section: Introductionmentioning
confidence: 99%